A comparative study of activated carbon aerogel and commercial activated carbons as electrode materials for organic electric double-layer capacitors. (June 2018) - Yang, Inchan; Kwon, Dahye; Kim, Myung-Soo; Jung, Ji Chul
Abstract: In this study, we thoroughly compared the electrochemical performances of activated carbon aerogel (ACA) and commercial activated carbons (CACs) as electrode materials for organic electric double-layer capacitors (EDLCs) to investigate the feasibility of ACA for commercial applications. The capacitive behavior of carbon materials as EDLC electrodes is strongly influenced by their specific surface areas and electronic resistances, which are determined by several preparation factors, including raw materials and activation methods. Unlike CACs, which have only micropores, ACA has both abundant micropores and mesopores, leading to a high surface area and low density. ACA also shows relatively low electronic resistance because of its three-dimensional structural features. Accordingly, ACA exhibits considerable capacitance at a low charge–discharge rate and excellent performance even at a high charge–discharge rate, indicating that ACA is a promising carbon material for organic EDLC electrodes. Furthermore, this comparison study clearly demonstrates that newly developed carbon materials for commercially advanced EDLC electrodes should exhibit both high specific surface area and low electronic resistance. Graphical abstract: Image 1